O fortalecimento da indústria de defesa do Brasil - Israel de Oliveira Andrade; Edison Benedito da Silva Filho; Giovanni Hillebrand; Marcelo Colus Sumi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The aim of this study is to discuss the resurgence of the Brazilian defense industry in the last decade. It analyzes the recent historical trend and the prospects created for its companies from the resumption of government policies towards the defense sector, as well as the challenges posed to the success of this revitalization process.
Keywords: L64; L52; O38; 330; Defense Industrial Base; industrial policy; technological innovation; national defense and sovereignty